PROFITABILITY OF ENTERPRISE IN THE CONDITIONS OF WARTIME: THREATS AND OPPORTUNITIES - Oliinyk, Nataliia; Lyzhenkova, Tetiana (Social Economics, 2024)
The purpose of the article is to form a clear understanding of the approaches to calculating the profitability of domestic enterprises in wartime conditions, to analyze the current state, and to determine the directions for increasing the profitability of logistics company «Nova Post». During the course of the work, general research methods such as comparison, statistical grouping, structuring, forecasting, and a systematic approach were applied.The conducted research provides grounds to establish that at the current stage of economic development, the profitability indicator plays a leading role in the analysis of enterprises' activities. The importance of this indicator is revealed during the analysis of the activities of economic entities in wartime conditions, as it allows for the most comprehensive and detailed assessment of resource efficiency and overall profitability of the enterprise, considering certain challenges in the legal, economic, and socio-political environment of the state. It has been established that under peaceful conditions and market economy (throughout the country), as well as under hybrid warfare conditions in the part of the territory where market relations are maintained and there are no military operations, three groups of indicators should be used to calculate enterprise profitability: cost, income, and resource. Under the introduction of martial law and full-scale military operations, it is advisable to calculate enterprise profitability based on the profitability indicators of the enterprise personnel, as the national economy during the war effectively switches to a command-administrative system. For the successful development of the logistics company «Nova Post», it is necessary to constantly work on finding appropriate directions for increasing its income and the level of profitability. If the enterprise aims to maximize profit, it must either reduce expenses or increase net revenue. The most effective directions are: increasing the number of parcel terminals; selection of qualified and responsible employees; return of the bonus system; expansion of branches in other countries, particularly in Germany. A project to open 8 delivery service offices of logistics company «Nova Post» on the territory of Germany has been proposed and substantiated.